Akumulasi Logam Berat Pb dan Cd dalam Sedimen dan Hubungannya dengan Biota Laut di Perairan Tulehu Ambon - Nur Alim Natsir; Yusrianti Hanike; Asyik Nur Allifah Af (Biotropic : The Journal of Tropical Biology, 2021)
The purpose of this study was to determine the Pb and Cd heavy metal content in sediments and their relationship with marine biota in Tulehu waters. The method used in the study was a survey by sampling at three research stations based on the representation of different characteristics at the study site. Station 1 at Tulehu Port 1 (non-operating and anthropogenic ship docker), Station 2 Tulehu Port 2 (ferry port) and Station 3 at Muara Sungai along Tulehu waters. The heavy metal content of Pb and Cd was measured using AAS (Atomic Absorption Spectroscopy). The heavy metal content of Pb and Cd has a effect on abundance and diversity of marine biota in Tulehu waters. This is evidenced by the Pb regression of marine biota abundance and diversity with values ​​r = 0,894 and Cd = 0.895. Increased content of heavy metals in sediments was followed by a decrease in the diversity of marine life in Tulehu waters.